Mycelial growth and germanium uptake by four species of ganoderma - Chow, Chin Tong; Pei, Joo Chong (Universiti Putra Malaysia Press, 1996)
Four Ganoderma species (G. tsugae, G. subamboinense var. laevisporium, A TCC 52419, G. tropicum and G. lucidum) were incubated in liquid medium containing different concentrations of germanium (Ge) for up to 20 days at 28 C. Increasing the Ge concentration of the medium resulted in a gradual decrease in the growth of the fungal mycelium. However, the Ge content in the mycelium increased with increasing Ge concentration. Different species recorded different levels of tolerance towards the Ge. In each case, the optimum concentration of the incorporated Ge in the medium was established as 100 mg/l for both optimal uptake of Ge by the fungal mycelium and optimal mycelial growth.